The Routledge Handbook of Policy Tools (Taylor & Francis, 2022)
This handbook provides a unique, systematic and comprehensive overview from leading experts in the field of the policy-making tools deployed at all the phases of the policy process. It covers the fundamentals of both new and established policy tools — from regulation and public enterprises to subsidies and information campaigns, as well as new tools such as, social impact investing, nudges, crowdsourcing, co-production and new digital governance and data analysis techniques.